A guide to genetic counseling - Uhlmann, Wendy R., 1961-; Schuette, Jane L., 1956-; Yashar, Beverly M. (John Wiley & Sons, 2009)
The first book devoted exclusively to the principles and practice of genetic counseling--now in a new edition First published in 1998, A Guide to Genetic Counseling quickly became a bestselling and widely recognized text, used nationally and internationally in genetic counseling training programs. Now in its eagerly anticipated Second Edition, it provides a thoroughly revised and comprehensive overview of genetic counseling, focusing on the components, theoretical framework, and unique approach to patient care that are the basis of this profession. The book defines the core competencies and covers the genetic counseling process from case initiation to completion--in addition to addressing global professional issues--with an emphasis on describing fundamental principles and practices. Chapters are written by leaders in the field of genetic counseling and are organized to facilitate academic instruction and skill attainment. They provide the most up-to-date coverage of: The history and practice of genetic counseling Family history Interviewing Case preparation and management Psychosocial counseling Patient education Risk communication and decision-making Medical genetics evaluation Understanding genetic testing Medical documentation Multicultural counseling Ethical and legal issues Student supervision Genetic counseling research Professional development Genetics education and outreach Evolving roles and expanding opportunities Case examples A Guide to Genetic Counseling, Second Edition belongs on the syllabi of all medical and human genetics and genetic counseling training programs. It is an indispensable reference for both students and healthcare professionals working with patients who have or are at risk for genetic conditions.